Cultural Schemas of Religion, Science, and Law in Talk About Social Controversies1. Issue 2 (22nd February 2017) - Edgell, Penny; Hull, Kathleen E.
Abstract : We analyze cultural schemas of religion, science, and law reflected in the way ordinary citizens discuss contemporary social controversies and assess whether these schemas accord with a modernization narrative or whether people's experiences with each of these institutional arenas lead them to adopt realistic or critical schemas not predicted by modernization accounts. Focus group participants in three metropolitan areas were asked to talk about one of three vignettes on faith‐based prison ministries, parents' refusal of medical treatment for a child on religious grounds, or preimplantation genetic diagnosis of human embryos. We find that people's everyday experiences, grounded in specific institutional contexts, produce perceptions of the domains of religion, science, and law that are not fully captured by the modernization account. Further, our findings illustrate that schemas of law, science, and religion are varied and evoked by social context and the specific issues under consideration. Schemas that do not fit the modernization framework provide a way for people to address concerns about power and effectively level the playing field between more and less rationalized social domains. Future research on a broader range of issues is needed to develop a theory of when different schemas of law, science, and religion are activated.